2020
DOI: 10.1007/s11356-020-09069-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of azamethiphos and dimethoate degradation using chlorine dioxide during water treatment

Abstract: Chlorine dioxide (ClO 2) degradation of the organophosphorus pesticides azamethiphos (AZA) and dimethoate (DM) (10 mg/L) in deionized water and in Sava River water was investigated for the first time. Pesticide degradation was studied in terms of ClO 2 level (5 and 10 mg/L), degradation duration (0.5, 1, 2, 3, 6, and 24 h), pH (3.00, 7.00, and 9.00), and under light/dark conditions in deionized water. Degradation was monitored using high-performance liquid chromatography. Gas chromatography coupled with triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…The main reactive site of ametryn herbicide and methiocarb pesticide during ClO 2 oxidation was the sulfur center in their molecules [47,49]. ClO 2 oxidation of two organophosphorus pesticides started with an attack on the amide group of azamethiphos and the phosphinothioyl group of dimethoate [16].…”
Section: Reactive Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reactive site of ametryn herbicide and methiocarb pesticide during ClO 2 oxidation was the sulfur center in their molecules [47,49]. ClO 2 oxidation of two organophosphorus pesticides started with an attack on the amide group of azamethiphos and the phosphinothioyl group of dimethoate [16].…”
Section: Reactive Sitesmentioning
confidence: 99%
“…Similarly, during the ClO 2 oxidation of the carbamate pesticide of methiocarb (MC), methiocarb sulfoxide and methiocarb sulfone were generated by losing HClO 2 and HOCl from the intermediate adduct of MC-ClO 2 -OH, respectively, which was first formed around the sulfur center of methiocarb [49]. Pergal, et al [16] studied the ClO 2 oxidation of two organophosphorus pesticides and found the successive attack on the amide group and the sulfide group in azamethiphos, leading to the break of the amide group and S-C bond, and the hydroxylation of the phosphinothioyl and then decarbonyl in dimethoate.…”
Section: Degradation Pathwaysmentioning
confidence: 99%
“…In order to minimize environmental risks originating from the presence of the pesticide, it would be judicious to develop effective technologies that ensure successful and simple degradation of these compounds (Pergal et al, 2020). Biodegradation is an efficient green remediation method of many types of xenobiotic chemicals by microorganisms that grow in different ecosystems including incompatible extreme conditions (Sarnaik, 2004).…”
Section: Introductionmentioning
confidence: 99%